An Ecological, Participatory, Integral and Contextualized Model (EPIC Model) of Family-School Connection: A Preliminary Analysis - Saracostti, Mahia; Lozano-Lozano, José Antonio; Miranda, Horacio; Lara, Laura; Martella, Diana; Reininger, Taly (Frontiers in Psychology, 2020)
There are several programs that aim to strengthen the bond between families and schools that have shown a positive impact on this relationship as well as its effectiveness in improving academic and socioemotional child indicators. Most of the studies in this area come from Anglo-Saxon countries while in Latin America research is still scarce. Thus, this study aims to assess the influence of implementing an Ecological, Participatory, Integral and Contextualized Family-School Collaboration Model (EPIC) on family involvement, social-emotional development, and cognitive test outcomes in children in elementary school. Three possible hypotheses have been considered: 1) The EPIC Family-School Collaboration Model will have a positive and significant influence on the level of family involvement; 2) The EPIC Family-School Collaboration Model will have a positive and significant influence on the results of some cognitive tests; and; 3) The EPIC Family-School Collaboration Model will have a positive and significant influence on child social-emotional development. The study included 171 students who attended second and third elementary grades in schools in Chile during 2017 and fourth and fifth grades during 2019. The children were between 7 and 12 years old (M = 8.17, SD = .98), during 2017 and between 9 and 14 years old (M = 9.88, SD = .99), during 2019. The results show that the EPIC Family-School Collaboration Model has a positive and significant influence on the level of home-based involvement, memory and attention and intrapersonal skills in the first cycle of elementary education.